Sequencing and Genomic Diversity Analysis of IncHI5 Plasmids - Liang, Quanhui; Jiang, Xiaoyuan; Hu, Lingfei; Yin, Zhe; Gao, Bo; Zhao, Yuee; Yang, Wenhui; Yang, Huiying; Tong, Yigang; Li, Weixuan; Jiang, Lingxiao; Zhou, Dongsheng (Frontiers in Microbiology, 2019)
IncHI plasmids could be divided into five different subgroups IncHI1–5. In this study, the complete nucleotide sequences of seven blaIMP- or blaVIM-carrying IncHI5 plasmids from Klebsiella pneumonia, K. quasipneumoniae and K. variicola were determined and compared in detail with all the other four available sequenced IncHI5 plasmids. These plasmids carried conserved IncHI5 backbones composed of repHI5B and a repFIB-like gene (replication), parABC (partition), and tra1 (conjugal transfer). Integration of a number of accessory modules, through horizontal gene transfer, at various sites of IncHI5 backbones resulted in various deletions of surrounding backbone regions and thus considerable diversification of IncHI5 backbones. Among the accessory modules were the three kinds of resistance accessory modules, namely Tn10 and two antibiotic resistance islands designated ARI-A and ARI-B. These two islands, inserted at two different fixed sites of IncHI5 backbones, were derived from the prototype Tn3-family transposons Tn1696 and Tn6535, respectively, and could be further discriminated as various intact transposons and transposon-like structures. The ARI-A or ARI-B islands from different IncHI5 plasmids carried distinct profiles of antimicrobial resistance markers and associated mobile elements, and complex events of transposition and homologous recombination accounted for assembly of these islands. The carbapenemase genes blaIMP-4, blaIMP-38 and blaVIM-1 were identified within various class 1 integrons from ARI-A or ARI-B of the seven plasmids sequenced in this study. Data presented here would provide a deeper insight into diversification and evolution history of IncHI5 plasmids.